Doskonałość w zarządzaniu - Kurowicki, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The study presents considerations regarding the concept of perfection in management in the context of output earned in the domain of philosophy and aesthetics specifically. Next, conclusions drawn from the above analysis were transferred into the field of management putting particular emphasis on the aspects related to environment management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 23-32